The Effectiveness of the TEACCH Model in Improving Joint Attention in Early Childhood Autistic Children: A Case Study at SLB River Kids - Yenni, Safrina; Setyosari, Punaji; Degeng, Nyoman Sudana; Sulthoni (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study aimed to evaluate the effectiveness of the Treatment and Education of Autistic and Related Communication Handicapped Children (TEACCH) model in improving joint attention skills in early childhood autistic children at SLB Autisme River Kids in Malang City. The TEACCH model emphasizes structured learning environments to enhance comprehension for autistic children. This approach involves physical structure, where learning spaces are clearly organized to minimize confusion and provide predictability. Visual schedules help children understand the sequence of activities and prepare them for transitions between tasks. Structured tasks ensure that activities are presented systematically, allowing children to complete them independently. Additionally, visual supports, such as images, symbols, or text-based cues, assist in reinforcing instructions, fostering autonomy, and reducing anxiety in the learning process. Data were analyzed using reduction, display, and inference techniques, with source triangulation to ensure validity. The results of the study showed that the TEACCH approach significantly (p < 0.05) improved joint attention skills in autistic children. Subjects demonstrated improvements in sharing attention with teachers or peers, an enhanced ability to follow visual instructions, and a reduction in maladaptive behaviors. The discussion highlighted that visual structures provide clarity, reduce anxiety, and increase children's participation in learning. However, this study confirms that a visually structured approach should be widely implemented in inclusive schools to support the social and communicative development of autistic children. The findings suggest that TEACCH-based interventions can serve as an effective educational strategy, not only in special education settings but also in mainstream classrooms aiming to accommodate neurodiverse learners.